2019
DOI: 10.3390/met9111181
|View full text |Cite
|
Sign up to set email alerts
|

Texture Evolution in Biocompatible Mg-Y-Re Alloy After Friction Stir Processing

Abstract: The presented study deals with the investigation of biocompatible WE 43 Mg-based alloy processed via the combination of rotary swaging (RS) and friction stir processing (FSP) at three different rotational speeds of 400 RPM, 800 RPM, and 1200 RPM. The structure observations primarily focused on texture development and characterizations of grain sizes and grain boundaries. The results showed that swaging plus processing at 400 RPM and 1200 RPM lead to substantial recrystallization and grain refinement. The fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The addition of REEs significantly contributes to the corrosion and mechanical properties of the REEs-containing Mg alloys and is common in alloys in various applications. 89 The alloying addition of REEs is extensively used to modify the Mg-based alloy structure. These dominant alloying additions include Sc and Y, along with the 15 lanthanides: La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu, which may further be divided into the light RREs or heavy RREs.…”
Section: Mixture Of Mg and Rresmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of REEs significantly contributes to the corrosion and mechanical properties of the REEs-containing Mg alloys and is common in alloys in various applications. 89 The alloying addition of REEs is extensively used to modify the Mg-based alloy structure. These dominant alloying additions include Sc and Y, along with the 15 lanthanides: La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu, which may further be divided into the light RREs or heavy RREs.…”
Section: Mixture Of Mg and Rresmentioning
confidence: 99%
“…Due to the low galvanic potential of Mg, the alloying additions must avoid the tendency toward forming intermetallic phases with substantially higher galvanic potentials, which leads to accelerated cathodic kinetics. The addition of REEs significantly contributes to the corrosion and mechanical properties of the REEs‐containing Mg alloys and is common in alloys in various applications 89 . The alloying addition of REEs is extensively used to modify the Mg‐based alloy structure.…”
Section: Progress In Mg‐based Screwmentioning
confidence: 99%
“…Furthermore, TEM examinations revealed that the coarse Mg 2 Si precipitates in the as-cast A356 sample disappeared after FSP, indicating the dissolution of most of the Mg 2 Si precipitates during FSP. FSP was found to be generally beneficial for dissolution of precipitates and structure homogenization [59].…”
Section: Friction Stir Processing Of Similar/dissimilar Alloys/metalsmentioning
confidence: 99%
“…Although numerous SPD processes have been introduced, not all the existing methods can be listed here owing to the continuing research in this field. However, the examples are high pressure sliding [14], high pressure tube twisting [15], friction stir processing [16], equal channel angular drawing [17], ECAP-partial back pressure [18], accumulative back extrusion [19], accumulative roll bonding [20], accumulative spin bonding [21], constrained groove pressing [22], constrained studded pressing [23], parallel tubular channel angular pressing [24], tube channel pressing [25], elliptical cross-section spiral equal-channel extrusion [26], C-shape equal channel reciprocating extrusion [27], half channel angular extrusion [28], cyclic extrusion compression [29], cyclic closed die forging [30], cyclic expansion extrusion [31], cyclic extrusion compression angular pressing [32], (variable lead) axi-symmetric forward spiral extrusion [33,34], forward shear normal extrusion [35], rotary extrusion [36], torsion extrusion (TE) [37], twist extrusion (TE) [38], simple shear extrusion [39], continuous shearing [40], continuous confined strip shearing [41], continuous frictional angular extrusion [42], repetitive corrugation straightening [43], severe torsion straining [44], and so on.…”
Section: Severe Plastic Deformation Processesmentioning
confidence: 99%